Production Of Fructosyltranferase By Penicillium Simplicissimum In Submerged Culture - Mortan, Siti Hatijah (2010)
Fructosyltransferase (FTase) is an enzyme responsible for the production of fructooligosaccharides (FOS). FOS is an important ingredient in the cosmetic, agrochemical, pharmaceutical and food industries. Recent increase in the demand of FOS has led to new search of FTase producing microorganism and a low cost substrate. Seventeen fungal isolates from different genera (Trametes, Pycnoporous, Lentinus, Schizophyllum, Penicillium, Aspergillus and Trichoderma) were evaluated for FTase production. Penicillium simplicissimum was found to attain the highest cell growth at 3.8 g/L and FTase activities of 506 IU/ml for extracellular and 128 IU/ml for intracellular, respectively. Sugarcane juice was found to have the highest sucrose concentration at 1.249×103 g/L among the seven sources of local sugar tested.